Effectiveness and safety analysis of SanHanHuaShi granules for the treatment of coronavirus disease 2019: Study protocol and statistical analysis plan for a randomized, parallel-controlled, open-label clinical trial - Liu, Yangyang; Chen, Xi; Wang, Hongan; Yao, Chensi; Gou, Xiaowen; Gao, Zezheng; Sun, Linlin; Liu, Dan; Tang, Cheng; Wei, Yu; Ding, Qiyou; Yang, Haoyu; et al. (Frontiers in Pharmacology, 2022)
Background: Coronavirus disease 2019 (COVID-19) has constituted an ongoing pandemic globally since its outbreak in late December 2019. As of May 2nd, 2022, COVID-19 has caused more than 510 million infections and 6.23 million deaths around the world, posing a major threat and challenge to human health worldwide. The practice of traditional Chinese medicine (TCM), which has a unique theoretical system, has a history of treating plague for thousands of years. Importantly, TCM has made a significant contribution and value to the response to COVID-19. SanHanHuaShi (SHHS) Granules is a Chinese herbal formula used to prevent and treat COVID-19. A previous retrospective cohort study has shown that SHHS can significantly reduce the rate of mild and moderate COVID-19 patients to severe. However, there is an absence of high-quality RCT to confirm the clinical effectiveness of SHHS. Therefore, a clinical study protocol and statistical analysis plan are designed to investigate the efficacy and safety of SHHS for the prevention and treatment of COVID-19. Methods and analysis: The study is designed to be a 7-day, randomized, positive-drug parallel-controlled, open-label, non-inferiority clinical trial. A total of 240 patients with mild and moderate COVID-19 will be enrolled and randomly allocated to SanHanHuaShi granules or LianHuaQingWen granules treatment in a 1:1 ratio. Disease classification, vital signs, SARS-CoV-2 nucleic acid testing, symptoms, medication, adverse events, and safety assessments will be recorded at each visit. The primary outcome is the rate of clinical symptoms recovery. The secondary outcomes include recovery time of clinical symptoms, SARS-CoV-2 nucleic acid testing negative conversion time and negative conversion rate, hospitalization time, antipyretic time, the conversion rate of turning to severe cases, the time and rate of single symptom recovery. Adverse incidents will be documented, as well as safety assessments. All data will be analyzed using a predetermined statistical analysis plan, including our method to missing data imputation, primary and secondary outcome analyses, and safety outcomes. Discussion: The current study results will ultimately provide more robust evidence to confirm the efficacy and safety of SHHS in the treatment of COVID-19.